2021
DOI: 10.5812/ijcm.107678
|View full text |Cite
|
Sign up to set email alerts
|

Possible Nutrition-Related Mechanisms of Metabolic Management in Cancer Treatment

Abstract: Context: Somatic mutation theory has been considered as a potential cause for cancer. However, major inconsistencies with the gene theory have necessitated serious reconsideration of this assumption. According to these inconsistencies, cancer may be considered as a metabolic disorder. According to the mitochondrial metabolic theory, substrate-level phosphorylation has been suggested to be superior to oxidative phosphorylation in cancer cells. Cancer metabolic therapies such as ketogenic diets (KD) and limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In previous articles, we discussed about glucose and glutamine restrictions along with the increase in non-fermentable ketones for cancer treatment [50][51][52][53]. It is suggested that TMAO Should be considered in dietary interventions for cancer prevention and treatment purposes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous articles, we discussed about glucose and glutamine restrictions along with the increase in non-fermentable ketones for cancer treatment [50][51][52][53]. It is suggested that TMAO Should be considered in dietary interventions for cancer prevention and treatment purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylcholine acyltransferase 1 (LPCAT1) converts LPC to PC, and it is overexpressed in breast cancer with poor prognosis [143], which demonstrates that a higher level of PC is associated with a high risk of breast cancer. In addition, a study conducted a metabolomics analysis in a large cohort of women and identified several metabolites that were positively associated with breast cancer risk, including sphingomyelin (d18:1/18:0), phosphatidylcholine (16:0/18:1), and lysophosphatidylcholine (C17:0) [13,144]. Another study reported that high levels of circulating SFA, particularly myristic acid (14:0), are correlated with an increased risk of breast cancer [135].…”
Section: Metabolites Of Fatmentioning
confidence: 99%